A Unified Framework for Detection of Suspicious and Anomalous Beahvior from Spatio-Temporal Traces - Kaluža, Boštjan (Informatica, 2014)
This paper presents a summary of the doctoral dissertation of the author on the topic of learning patternsof agent behavior from sensor data.